Examining #RacunTikTok Content and Peer Group Influence on Gen Z Impulsive Buying - Amali, Muhammad Thoyib; Farohi, Muhammad Salman (Universitas Prof. Dr. Moestopo (Beragama), 2025)
The phenomenon of content with the hashtag #RacunTikTok has changed consumer behavior in making online purchases, especially among Gen Z. This content functions as a product recommendation and the main trigger for impulsive purchases. Another important factor influencing this phenomenon is peer group, where Gen Z is considered to have high group cohesiveness, highly influenced by recommendations from peers and their online communities. This study aims to analyze the effect of #RacunTikTok content and peer groups on Gen Z's impulsive buying behavior in TikTok Shop. This study employs an explanatory quantitative approach using a multiple regression model analyzed with the SmartPLS program. Data were collected through a survey of 100 Gen Z TikTok users who frequently make online purchases via TikTok Shop. The study results show a positive and significant effect of #RacunTikTok content on impulsive buying behavior. At the same time, peer group does not significantly affect impulsive buying. Still, when combined, #RacunTikTok content and peer group has a positive and significant effect on impulsive buying. Furthermore, as a form of managerial implication, marketers or content creators of #RacunTikTok should create more attention-grabbing content by paying attention to the effectiveness of marketing content or collaborating with digital influencers to increase content exposure.